El proyecto de vida en las dimensiones educativa y laboral de los adolescentes entre 15 y 18 años victimas del desplazamiento forzado ubicados en el municipio de Malambo Atlántico (2009)
The General mission of the investigation project, was to describe the project of life in the educative and labor dimension of the adolescent victims of the forced displacement located in the municipality of Malambo. The theoretical foundation is sustained in the Theory of the Social Action of Thomas Luckmann. The methodology of the project was framed in a descriptive type of investigation. The population was six (6) adolescents, between the age of 15 and 18 years old. For the technique of harvesting of the information it was used the semi-structured interview and histories of life. Within the obtained results the existence of a life project was product of the relation between the fantasy and the project from the prehistory of the adolescents interrelated with a vision and history of life, framed in desires of overcoming and improvement of its present conditions of life, that maintain a strong tendency to think about the present and to project to an immediate future, providing solution to the circumstances which they have priority in the present and moving the possibilities of thinking about problems and future solutions, starting off of its strengths and weaknesses, an identification exists of those who are, know the realities that favor and work against their dreams, and are conscious of the necessity to continue preparing itself for that future that wishes.